PELATIHAN KEADAAN DARURAT KEBAKARAN DI KM. RADHIKA PANGESTU - Fernando Ventino Noro; Muhammad Syafril Sunusi; Barnabas Fendy Tallu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the level of crew skills in handling fire emergency situations and to evaluate the effectiveness of fire drill implementation on board KM. Radhika Pangestu in order to improve maritime safety. A qualitative descriptive method was used, with data collected through direct observation during fire drill exercises and structured interviews with eight ship officers, including the Master, Chief Officer, Second Officer, Third Officer, Chief Engineer, and First, Second, and Third Engineers. The results indicate that the ship's officers demonstrate a good level of understanding of fire emergency procedures in accordance with SOLAS Convention and ISM Code standards. However, gaps were identified in terms of technical skills in operating firefighting equipment and mental readiness during emergency simulations. In one observed fire drill, a helmsman failed to effectively operate a foam-type APAR, resulting in a 15-minute delay beyond the standard 5-minute target. These findings emphasize the need for enhanced training quality, more realistic drill scenarios, and continuous evaluation to improve crew preparedness and maritime safety.